84 Cytoreduction followed by hyperthermic intraperitoneal chemotherapy (CRS+HIPEC) in advanced peritoneal carcinomatous (APC) at the american university of beirut medical center (AUBMC): a retrospective review. (18th September 2019) - Seoud, M; El Housheimi, A; Shamseddine, A; Khalifeh, M; Jaafar, I; Jamali, F
Abstract : Objectives: To review the outcome of patients with APC who underwent CRS+HIPEC by the HIPEC team at the AUBMC. Methods: All patients with APC were evaluated by the HIPEC team for eligibility and the majority had either gastrointestinal or gynecological malignancies. We retrospectively reviewed data related to their demographics/tumor origin/surgical completeness/adverse events/outcome. Results between 2007 and 2018, 53 patients (45% were females) had CRS and HIPEC. 20 (37.6%) had Pseudomyxoma peritonei (PMP), 12 (23%) ovarian cancer, 14 (26.4%) colorectal cancer, 4 (7.5%) had gastric cancer, 2 (3.7%) had Mesothelioma and one (1.8%) Desmoplastic round cell tumor. Operative and Postoperative demographics and survivals are shown in tables 1 and 2. Median progression free (PFS) and overall survival (OS) are expressed in months. Conclusions: We report the successful establishment of an active peritoneal surface malignancy multidisciplinary treatment program with results comparable to other centers. Careful patient selection, a multidisciplinary approach and proper surgical training and technique are essential for the success of such a program.